THE EFFECT OF RANDOMIZED, VARIABLE-INTENSITY EXERCISES ON SOME PHYSIOLOGICAL VARIABLES OF ADVANCED BASKETBALL PLAYERS - Waleed Kamil Rashoody (Scholars Digest Publishing, 2025)
The researcher aimed to use randomized, irregular-intensity exercises and identify their physiological effects on advanced basketball players. He aimed to randomize the various exercises to measure the direct impact of these exercises on the players. The researcher intentionally selected the research sample, which consisted of 12 advanced basketball players in the Diwaniyah Governorate. The researcher then tested the homogeneity of these players. The researcher used the experimental method using a single-group approach to suit the research project. The researcher conducted and implemented the research items on the target sample, including variables such as heart rate, maximum oxygen consumption, oxygen debt, and oxygen deficit. The physical exercises took place over a period of four weeks, with four training sessions per week. The duration of the training session ranged approximately 60 minutes, during which the research exercises targeted by the researcher were implemented. The aim was to determine the clear impact of these exercises on the studied variables, and to determine whether the random exercises had a significant impact. These variables were examined in order to accurately design training programs in light of the results obtained in this study. The researcher then drew his most important conclusions and recommendations based on the results obtained in this study, which demonstrated that exercises, even if random and varying in intensity, have a clear impact on the body's systems and physiological variables. In light of the results obtained, the researcher concluded that random physical exercises have an impact on the body's physiological variables, even if they are random and unregulated
Keywords: Random exercises: These are exercises that vary in intensity and impact the players, such that the training intensity increases at times and decreases at other times.